Diversity and functional analysis of gut microbiota reveal ecological adaptations in the inquilinism of Ancistrotermes dimorphus and its host Macrotermes barneyi - Lei, Wenzhuo; Qin, Zhifang; Jia, Bao; Lu, Wen; Yang, Juan; Gao, Qionghua (Frontiers in Microbiology, 2025)
Inquilinism describes an interesting interspecific interaction in termite ecosystems wherein an inquiline species inhabits the host’s nest structure. In this context, gut microbiota play a crucial role in mediating the ecological relationship. The facultative inquiline Ancistrotermes dimorphus (Termitidae: Macrotermitinae) frequently inhabits nests of the host Macrotermes barneyi but can also establish independent colonies. We used 16S rRNA sequencing to compare the gut microbiota of A. dimorphus and M. barneyi in independent and inquilinism nests, assessing microbial diversity and composition. Gut microbiota diversity increased under inquilinism, with greater microbial similarity between A. dimorphus and M. barneyi in shared nests. Furthermore, inquilinism altered microbial function, increasing taxa linked to environmental adaptation while reducing those involved in energy metabolism, suggesting potential metabolic trade-offs. Beta diversity analysis indicated that inquilinism drives the gut microbiota adaptation between the host and inquiline. These findings reveal how gut microbiota mediates host-inquiline interactions, advancing our understanding of microbial adaptation in social insect symbiosis.